The Use of External Auditor to Data Mining as an Artificial Intelligence Technology to Examine the Internal Control Systems in an Electronic Business Environment - Faez Abdulhasan Jasim Allami (Peerian Journals Publishing, 2022)
This research clarified the importance of the external auditor’s use of one of the modern tools of artificial intelligence applications in the audit process, i.e., data mining technology in the electronic business environment. Therefore, this research gauged the contribution of artificial intelligence applications in diagnosing the strengths and weaknesses of electronic control systems in an electronic business environment. It also investigated the contribution of artificial intelligence to external auditor in reducing auditing risks. The study reached that: artificial intelligent applications can be used in various fields, including in They enjoy a number of advantages that increase the need for them .accounting and auditing Furthermore, they contribute to developing the role of the .with the development of technology auditors and improving the quality of their performance. External auditor employs artificial intelligence with data mining technology to provide a new mechanism that will improve and Finally, it is recommended to include artificial intelligent in the .achieve audit objectives curricula and that the external auditor’s report should contain a paragraph which states the extent and type of modern technology used in the audit
Keywords: Artificial intelligence; data mining; electronic internal control systems; auditor